2018
DOI: 10.1002/jcp.26466
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative burden in familial hypercholesterolemia

Abstract: Familial hypercholesterolemia (FH) is a genetic disorder characterized by high serum levels of low-density lipoprotein cholesterol (LDL-c). FH is characterized by accelerated development of atherosclerosis and represents the most frequent hereditary cause of premature coronary heart disease. Mutations of the LDL receptor gene are the genetic signature of FH, resulting in abnormal levels of circulating LDLs. Moreover, FH promotes the generation of reactive oxygen species (ROS) which is another key mechanism inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 119 publications
1
30
0
1
Order By: Relevance
“…Oxidative stress and inflammation are important causes of cardiovascular disease [ 38 , 39 ]. Studies have shown that hyperlipidemia causes cardiac damage by increasing oxidative stress and that reactive oxygen species (ROS) play an important role in this damage [ 40 ]. Furthermore, it has been confirmed that excessive accumulation of ROS can transmit the signal to downstream ROS-sensitive signaling pathways, such as NF- κ B, ERK1/2, p38 MAPK, and autophagy-related signaling to induce pathological cardiac hypertrophy [ 41 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress and inflammation are important causes of cardiovascular disease [ 38 , 39 ]. Studies have shown that hyperlipidemia causes cardiac damage by increasing oxidative stress and that reactive oxygen species (ROS) play an important role in this damage [ 40 ]. Furthermore, it has been confirmed that excessive accumulation of ROS can transmit the signal to downstream ROS-sensitive signaling pathways, such as NF- κ B, ERK1/2, p38 MAPK, and autophagy-related signaling to induce pathological cardiac hypertrophy [ 41 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, abnormal OS contributes to metabolic disorders and carcinogenesis. Therefore, improvement of OS status may be prone to alleviate atherogenesis as well as diabetes mellitus and cancer …”
Section: Introductionmentioning
confidence: 99%
“…Oxidative stress is a leading mechanism of glutamate neurotoxicity and immune responses, which were shown to promote RGC death [39][40][41]. In the vasculature, oxidative stress is also a trigger factor of endothelial dysfunction in various cardiovascular diseases [42,43]. Hence, it is reasonable to assume that oxidative stress induced by IOP elevation may also affect the reactivity of blood vessels in the retina.…”
Section: Discussionmentioning
confidence: 99%